One-pot conversion of engineered poplar into biochemicals and biofuels using biocompatible deep eutectic solvents. Issue 23 (12th October 2022) - Kim, Kwang Ho; Mottiar, Yaseen; Jeong, Keunhong; Tran, Phuong Hoang Nguyen; Tran, Ngoc Tuan; Zhuang, Jingshun; Kim, Chang Soo; Lee, Hyunjoo; Gong, Gyeongtaek; Ko, Ja Kyong; Lee, Sun-Mi; Kim, So Young; et al.
Abstract : Integrating plant cell wall engineering and process consolidation using biocompatible deep eutectic solvents could enable the development of sustainable biorefineries that effectively utilize both carbohydrates and lignin. Abstract : Multidisciplinary approaches are needed to overcome the various technical and technoeconomic challenges that have hindered the development of sustainable biorefineries. Herein, we report on the one-pot conversion of transgenic poplar biomass into bioproducts using biocompatible deep eutectic solvents (DESs). Engineered poplar wood with elevated levels of cell-wall-bound p -hydroxybenzoate ( p HB) was processed using choline chloride–glycerol (ChCl–Gly) and betaine–glycerol (Bet–Gly), two non-conventional solvent systems. A metabolic engineering strategy that increased the abundance of terminal phenolic p HB groups on lignin resulted in transgenic poplar wood with reduced inherent recalcitrance. The engineered poplars, particularly those with the greatest levels of p HB, released more fermentable sugars and produced higher yields of bioethanol compared to wild-type trees following a one-pot treatment with ChCl–Gly. Equally important, the residual lignin was a rich source of alkylphenols upon hydrogenolysis, which highlights an important additional opportunity for lignin valorization. Our findings show how integrating plant cell wall engineering and process consolidation using biocompatible DESs could enable the development of sustainable biorefineries that effectively utilize both carbohydrates and lignin.